Clinical implications of cardiac hyperpolarized magnetic resonance imaging - Rider, O; Tyler, D (BioMed Central, 2013)
Alterations in cardiac metabolism are now considered a cause, rather than a result, of cardiac disease. Although magnetic resonance spectroscopy has allowed investigation of myocardial energetics, the inherently low sensitivity of the technique has limited its clinical application in the study of cardiac metabolism. The development of a novel hyperpolarization technique, based on the process of dynamic nuclear polarization, when combined with the metabolic tracers [1-(13)C] and [2-(13)C] pyruvate, has resulted in significant advances in the understanding of real time myocardial metabolism in the normal and diseased heart in vivo. This review focuses on the changes in myocardial substrate selection and downstream metabolism of hyperpolarized 13C labelled pyruvate that have been shown in diabetes, ischaemic heart disease, cardiac hypertrophy and heart failure in animal models of disease and how these could translate into clinical practice with the advent of clinical grade hyperpolarizer systems.